UBEZPIECZENIE TYTUŁU PRAWNEGO DO NIERUCHOMOŚCI NA PRZYKŁADZIE JEZIOR WYSTĘPUJĄCYCH W OBROCIE CYWILNOPRAWNYM - Sławomir Brózda; Michał Marszelewski (Zeszyty Prawnicze)
Real Property Title Insurance in Civil Law Transactions Concerning Lakes Summary The article presents title insurance for civil law transactions involving lakes. The purpose of this insurance is to compensate for financial losses in the event of legal defects relating to the ownership (title) of real property coming to light after the transfer of such ownership. The paper discusses the origins of title insurance, which comes from the USA, and accounts for its rapid development. The issues discussed include the concept of title insurance, its distinguishing features, and the scope of protection it offers. The authors conduct an analysis of a model title insurance for compliance with Polish law. The result they obtain is that this type of insurance meets the requirements imposed by the Polish legal order. They then move on to the applicability of title insurance to transfer of property ownership involving lakes, and show that title insurance can be a significant advantage protecting a buyer’s interests. This is all the more important because the legal disputes which may arise from the transfer of property ownership in civil law involve many aspects, require specialist knowledge, and can be expensive.